A análise comparativa de proteínas secretadas em helmintos revela diferenças de acordo com diferentes estilos de vida e hospedeiros - Yesid Cuesta Astroz (2015)
Comparative analyses of partially or completely sequenced genes and genomes in helminths are important to understand the genomic diversity and evolution of parasites and their hosts in terms of different selective pressures in their habitats. Proteins secreted by parasites are able to modify the host's environment and modulate their immune system. Little is known about the composition and variability of secreted proteins in different helminth species besides its contribution in the progress of the infection. In this project we predicted the in silico secretome across 44 helminth species (Nematoda: 31 species, Platyhelminthes: 13 species) aiming to understand the diversity and evolution of secretomes. Our results indicated secreted proteins associated with biological processes such as: infection, invasion, adhesion, immunoregulation (protease inhibitors, cytokines), among others. We also analyzed protein domains and domain architectures in secreted proteins to identify specific signatures associated with niches or hosts. Furthermore, cystatin family homologs were identified in three Schistosoma species and other Platyhelminthes. Cystatins are a family of cysteine protease inhibitors which are part of the secretome. The reconstruction of evolutionary relationships of these proteins allowed us to observe their diversity at the molecular level and gene duplications events, shaping their evolution over time. In summary, the development of this project contributed to the understanding of of helminth biology, including aspects of the host-parasite interaction. In the future, it will be possible to identify new molecular targets for the treatment or diagnosis of helminthiases.